2007
DOI: 10.1103/physreva.76.042306
|View full text |Cite
|
Sign up to set email alerts
|

Quantum speedup of classical mixing processes

Abstract: Most approximation algorithms for #P-complete problems (e.g., evaluating the permanent of a matrix or the volume of a polytope) work by reduction to the problem of approximate sampling from a distribution $\pi$ over a large set $\S$. This problem is solved using the {\em Markov chain Monte Carlo} method: a sparse, reversible Markov chain $P$ on $\S$ with stationary distribution $\pi$ is run to near equilibrium. The running time of this random walk algorithm, the so-called {\em mixing time} of $P$, is $O(\delta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
88
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 36 publications
3
88
1
Order By: Relevance
“…For odd-N cycles with no decoherence, they reported that M( ) ∼ N/ as compared to the upper bound of M( ) ∼ N log N/ 3 given in Aharonov et al (2001). Richter has recently confirmed this analytically (Richter 2007b).…”
Section: Effects In the Walk On The N-cyclesupporting
confidence: 51%
See 3 more Smart Citations
“…For odd-N cycles with no decoherence, they reported that M( ) ∼ N/ as compared to the upper bound of M( ) ∼ N log N/ 3 given in Aharonov et al (2001). Richter has recently confirmed this analytically (Richter 2007b).…”
Section: Effects In the Walk On The N-cyclesupporting
confidence: 51%
“…In fact, the proofs in Richter (2007b) are sufficiently general that they apply equally to the continuous-time walk as to the discrete-time walk. This fills the gap between small and large decoherence rates, and proves that continuous-time walks, with O(log(1/ )) decoherence or measurement events, mix in time O(N log(1/ )) on the cycle (and the d-dimensional torus).…”
Section: Effects In the Walk On The N-cyclementioning
confidence: 99%
See 2 more Smart Citations
“…The question whether a quantum speed-up to O(1/ √ δ log(1/π(x)) is possible has been examined in [9]. The author proposes a method based on quantum walks that decohere under repeated randomized measurements to attack this problem.…”
Section: Introductionmentioning
confidence: 99%